An Expeditious Asymmetric Synthesis of the Polyketide Unit Present in HIV-Inhibitory Depsipeptides Aetheramide A and B - Revu, Omkar; Prasad, Kavirayani R. (Synlett, 2014)
The enantioselective synthesis of the polyketide unit present in depsipeptides aetheramide A and B, which possess potent HIV-inhibitory activity, is accomplished from a chiral furyl carbinol.
Keywords: macrolactones; natural products; depsipeptides; HIV-inhibitors